Quantifying preferences and responsiveness of marine zooplankton to changing environmental conditions using microfluidics - Ramanathan, Nirupama; Simakov, Oleg; Arendt, Detlev (PLOS ONE, 2015)
Global environmental change significantly affects marine species composition. However, analyzing the impact of these changes on marine zooplankton communities was so far mostly limited to assessing lethal doses through mortality assays and hence did not allow a direct assessment of the preferred conditions, or preferendum. Here, we use a microfluidic device to characterize individual behavior of actively swimming zooplankton, and to quantitatively determine their ecological preferendum. For the annelid zooplankton model Platynereis dumerilii we observe a broader pH preferendum than for the copepod Euterpina acutifrons, and reveal previously unrecognized sub-populations with different pH preferenda. For Platynereis, the minimum concentration difference required to elicit a response (responsiveness) is ~1 μM for H+ and ~13.7 mM for NaCl. Furthermore, using laser ablations we show that olfactomedin-expressing sensory cells mediate chemical responsiveness in the Platynereis foregut. Taken together, our microfluidic approach allows precise assessment and functional understanding of environmental perception on planktonic behaviour.
Gesehen am 09.06.2017